Association between interleukin gene polymorphisms and the risk of pneumoconiosis: a systematic review and meta-analysis - Liu, Lu; Tian, Xiaowei; Guo, Yilin; Yu, Yanyan; Wang, Yamei; Wang, Wenjing; Meng, Jun; Li, Guifang; Sun, Xiaojuan (Frontiers in Medicine, 2025)
Numerous studies have demonstrated that interleukin (IL) plays an essential role in the development of chronic inflammatory diseases, especially in pneumoconiosis. The association between various IL gene polymorphisms and pneumoconiosis susceptibility has been investigated extensively, but the results remain controversial. A literature search was conducted using PubMed, EMBASE, Web of Science, Cochrane Library, China National Knowledge Infrastructure (CNKI), and Wanfang database to obtain relevant studies before 22 January 2025. Subsequently, odds ratios (ORs) with 95% confidence intervals (CIs) were used to evaluate the strength of correlations. A sensitivity analysis was performed to evaluate the robustness and reliability of the included studies. Overall, there was a significant association between IL-1RA +2018 and IL-6 -634 with the risk of pneumoconiosis. The IL-1RA +2018 variant was positively associated with an increased risk of pneumoconiosis among both Asians and Caucasians. In contrast, the IL-6 -634 genotype was associated with a lower risk of pneumoconiosis among Asians. Additionally, the IL-1RA +2018 genotype was significantly linked to a predisposition to coal workers’ pneumoconiosis (CWP) and silicosis. The IL-6 -634 mutant significantly decreased silicosis and CWP risk. Additional large-scale replication studies are needed to elucidate the precise role of various IL SNPs in the etiology of pneumoconiosis.